Synthesis and electrochemical properties of -Fe2O3 particles for energy storage devices - Bui Thi Hang; Tran Van Dang (Vietnam Journal of Science and Technology, 2023)
In this study, we fabricated α-Fe2O3 materials via a facile hydrothermal route to use as the active material for iron-based battery anode. The particle size of α-Fe2O3 is in a range of a few hundreds of nanometers to a few micrometers. The structural characteristics and particle size of the synthesized iron oxides were studied via X-ray diffraction (XRD) and scanning electron microscopy (SEM). The electrochemical behavior of iron oxide electrode was investigated by cyclic voltammetry (CV). The distribution of iron species was observed by Energy dispersive X-ray spectroscopy (EDS) measurement. Carbon was used as additive to improve the conductivity of α-Fe2O3/C composite electrode. The electrochemical measurements revealed that the prepared α-Fe2O3 particles provided the good cyclability. The EDS showed that iron species were dispersed on the carbon surface during discharge-discharge through the electrochemical dissolution-deposition process of iron.